Identification of spatial patterns and sources of heavy metals in greenhouse soils using geostatistical and positive matrix factorization (PMF) methods. (25th October 2021) - Meng, Min; Yang, Linsheng; Yu, Jiangping; Wei, Binggan; Li, Hairong; Cao, Zhiqiang; Chen, Qing; Zhang, Guoyin
Abstract: Greenhouse vegetable products are important dietary sources. Heavy metals in greenhouse soils are associated with food safety and public health. Therefore, heavy metals in greenhouse soils are of significant concern. This study used positive matrix factorization (PMF) and geostatistical analyses to assess possible sources and spatial distribution patterns of heavy metals in 248 greenhouse soil samples obtained from southern Hebei Province, China. The results showed that the mean arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb), and zinc (Zn) concentrations in the greenhouse soil samples were 13.5, 0.16, 74.3, 31.4, 0.03, 26.0, 156, and 98.0 mg/kg, respectively. Approximately 97.18%, 32.26%, 25.81%, 22.98%, 8.06%, 6.45%, 2.02%, and 0.40% of sample sites were contaminated with Cd, Cu, Hg, Zn, Cr, As, Pb, and Ni, respectively. The PMF indicated that Cd and Pb was mainly influenced by metal smelting activity; Cu and Zn accumulation in greenhouse soils was mainly from manure and chemical fertilizer application, while Ni, Cr, and As were strongly derived from natural sources. The spatial distribution patterns varied among metals, with Ni and Pb mainly controlled by natural factors, whereas Cd, Cu, Cr, and Zn were moderately to strongly influenced by fertilizer application. However, Pb is also affected by atmospheric deposition caused by industrial emissions. The spatial distribution of As is controlled by both natural and anthropogenic factors.